If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 177 = 6X + -46 Reorder the terms: 177 = -46 + 6X Solving 177 = -46 + 6X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-6X' to each side of the equation. 177 + -6X = -46 + 6X + -6X Combine like terms: 6X + -6X = 0 177 + -6X = -46 + 0 177 + -6X = -46 Add '-177' to each side of the equation. 177 + -177 + -6X = -46 + -177 Combine like terms: 177 + -177 = 0 0 + -6X = -46 + -177 -6X = -46 + -177 Combine like terms: -46 + -177 = -223 -6X = -223 Divide each side by '-6'. X = 37.16666667 Simplifying X = 37.16666667
| 2log(x-5)=0 | | 4+9x-11=3(3x-5) | | 5y^2-7y-6= | | 8(1-m)+2(4-m)=3(6-3m)-5(m-2) | | 3x-6x-34=0 | | -x(2)+7x=5 | | 8x-10=-3y+2 | | 1x+15=2x+10 | | 0=10000-10x | | 6x+4-5x-20=40 | | 9k+36k+35=0 | | x+3(4)=18 | | 2x-y+z=0 | | 72x*(x^5+y^2)= | | x^3+5x^2+24x=0 | | 1x+15=3x | | 72x(5x+2y)= | | 100x+50y+20z=3150 | | 8.2=y-3.9 | | 7(x-5)=3(4-x) | | 3+4=121 | | 26.5=n+2.08 | | x=11+6y | | 2LOG(X)-3LOG(X+7)= | | -3x-6(1+2x)=-111 | | 12x+30=3(4x-10) | | F(x)=-9x^2+7x+2 | | (3x^2-3xy^4)dx+(y^2-6x^2y^3)dy=0 | | 7y-6-2y+2=0 | | 2x+4(x+16)=130 | | 8m^2-11m+3=-5 | | 2r^2+3r-2+5r^2+8= |